ICT MANAGEMENT AND TELEGRAM BOT: IMPLEMENTATION OF INFORMATION SERVICES FOR DAAR EL HASANAH STUDENTS - Bakroni Latar; Encep Syarifudin; Shobri Shobri (IJGIE (International Journal of Graduate of Islamic Education), 2022)
This study describes the implementation of information technology system management and telegram bots in student services and information. The method used is descriptive qualitative. The study was conducted at the Daar El Hasanah Jawilan Civilization Islamic Boarding School, Serang Regency, Banten Province. The data is taken from primary and secondary data, which comes from documentation of Islamic boarding schools, relevant books, and reputable journals both internationally and nationally. Data collection techniques are through observation, in-depth interviews, document assessment, and focus group discussions. Data analysis is done through the process of editing, organizing, and interpretation. The results of the study show that the application of information technology system management and telegram bots is very effective in using services and information for Islamic boarding school students, which consists of academic, financial, library, staffing, reporting, computer-based exams, teacher info, student info, SMS gateway, and pavilion services. The study recommends that Islamic educational institutions such as Islamic boarding schools and madrasas take advantage of information technology's sophistication in providing services to users.